CITRA PLURALITAS DAN RELIGIUSITAS MASYARAKAT SASAK DI LOMBOK: TINJAUAN SOSIO-SEMIOTIK ATAS TE MELAK MANGAN - , Usup ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Problems of this assessment is the image of plurality and religiosity Sasak people who studied through the story TMM. The purpose of this study is to reveal the values of TMM stories relating to plurality and religiosity using semiotic theories of Roland Barthes. Based on the results of studies conducted on TMM story, a story on stage inventory code, the code is found the story a number of 649 pieces. At this stage the story with the meaning of the code based on the hermeneutic code, semik, symbolic, proaeretik, and culture, found some code that is cultural, namely the identity code, the code of acculturation, cultural diversity codes, the code diversity of religion and belief, the character feature code , and the code of power and authority figures that reflect the prototype of kings King of Majapahit. Based on the problems of plurality and religiosity in the story, found Sasak is a diverse society and interkulturalisme which can be grouped into three socio-cultural map, the character of the ideology of Islamic religious community residing in the territory of the Kingdom of the New Jero similar to the culture of the Madurese